Modern Instruments of Research Development: Global Expermnce and Lessons to be Taken - Čekanavičius, Linas; Samalavičius, Almantas (Ekonomika, 2005)
The spiritus movens of the research development is scientific excellence. Analysis of the global experience enables to single out several modem institutional channels for accumulation and promotion of excellence, namely centres and networks of excellence, and institutes for advanced studies. These institutional instruments are designed to foster research development via concentration of intellectual and physical resources for the solution of important problems of socio-economic development or for the achievement of significant break·through in the fundamental research.Centre of excellence is an institution uniting competent scientists coming together to assemble a critical mass of intellectual capacity and to address strategic research questions deemed vital to the social and economic development. Network of excellence is a formation integrating the intellectual abilities and research infrastructure of particular centres of excellence - it is therefore an “institution without walls” that is capable of achieving more than the sum of the individual efforts of the centers. Institutes of advanced studies are a unique strain of centres of excellence that provide a unique opportunity for both prominent scientists of a global scale and the perspective young researchers to engage into the advanced and frontier pushing research for a certain period of time away from their everyday routine.Although different in their organization these institutional forms of research are united by the common goal: to increase the complexity and interdisciplinarity of research, to overcome the national and institutional fragmentation of research and to achieve a positive synergetic effect by the means of accumulation of the “critical mass” of excellence. All institutions also carry out the essential function of upbringing a new generation of scientists, and to facilitate the international exchange of ideas and researchers.Even a short glance at the institutional infrastructure of research in Lithuania reveals in it many gaps that impede both the local research development and participation in the international programmes of research integration. The optimization of the current system with orientation towards the surveyed international models is deemed to be necessary for the further progress of science in Lithuania.